Diseminasi Teknologi Karbontech dengan Pengkayaan Mikroba pada Limbah Padi dan Jagung sebagai Pupuk Api (Biochar) di Kabupaten Sidrap, Sulawesi Selatan - Iradhatullah Rahim; Yadi Arodhiskara; Harsani Harsani; Sukmawati Sukmawati; Wahyuddin Wahyuddin; Nurananda Nurananda; Rini Rini; Maryam Maryam; Rahmat Muda; Muh Rustam (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
This activity aims to disseminate carbon tech technology and enrichment using microbes in agricultural waste into nutrient-rich biological charcoal. The products produced and the technology used was disseminated to farmers to utilize sandy land, which is marginal land in Ciro-Ciroe Village, Sidrap Regency, South Sulawesi. This activity also involved 5 students as participants in the Independent Study program in the MBKM program and members of the Mallawa Farmers Group. The implementation method is by conducting socialization and counseling about using organic matter to restore soil fertility. Demonstrations of activities were carried out starting from making biochar to application on sandy land with an area of 700 m2 as a demonstration plot for shallot cultivation. The results showed that the organic matter produced using carbon-tech technology had a neutral pH, namely 6.66‒7.22, the highest C content was in rice husk biochar applied by Pleurotus sp, namely 21.45, and the best maturity level was in corncob biochar + Pleurotus sp, namely 17. The highest N was in corn cob + Pleurotus biochar, the highest P content was in rice husk + Pleurotus biochar, while the highest K content was in corn cob + compost + Pleurotus biochar. These results indicate that applying microbial-enriched fire fertilizers and compost is very suitable for sandy land managed by farmers in Ciro-Ciroe, Sidrap Regency. This application is highly recommended for sandy land to produce superior commodities sustainably and environmentally friendly manner.